Design and Implementation of a Novel Modular Armed Advanced Robotic System (MAARS) (International Journal of Innovative Research in Computer Science & Technology, 2022)
A Modular Armed Advanced Robotic  System based on face recognition is intended for military  applications identifies the unidentified individuals in border  area or conflict zones or in any comparable location, and  conducts obstacle detection, bomb detection and implements  gun aiming system. Wi-Fi connection is carried to send the  message to the receiving system. This function is done by  algorithm or manually with the assistance of Lab view or  SSH (Secured Shell) software installed in recipient system.  This method is done out utilizing Raspberry Pi board with  ARM cortex A53 CPU and Arduino Uno microcontroller  (AtMega328P). The hardware comprises the ultrasonic  sensor, Bluetooth device, wireless camera, DC (Direct  Current) servo motor, and mechanical gripper. Unique single  ultrasonic sensor is automated to pursue the article, and  complete the article localization. A human-machine interface  is manufactured to remotely operate the transportable robot.  Through wireless connection and camera, the investigation  of a minute and punishing environment may be carried out.  Hardware explanation language is utilized in the controller  enterprise and the fringe I/O (input/output) circuit. Human machine interface is done via C language which can be useful  in various future studies.
Keywords: Military Applications; Raspberry Pi; Robotic System; Wi-Fi Network